2019
DOI: 10.3390/cells8050428
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serum Free Amino Acids in Head and Neck Cancers

Abstract: Despite distinctive advances in the field of head and neck squamous cell cancer (HNSCC) biomarker discovery, the spectrum of clinically useful prognostic serum biomarkers is limited. As metabolic activities in highly proliferative transformed cells are fundamentally different from those in non-transformed cells, specific shifts in concentration of different metabolites may serve as diagnostic or prognostic markers. Blood amino acids have been identified as promising biomarkers in different cancers before, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Lastly, newly developed circulating biomarkers such as free serum amino acids [38] could be compared to CTC or ctDNA detection for their prognostic value. Similarly, circulating extracellular matrix components have been evaluated as biomarkers for cancer diagnosis and prognosis in various tumor types [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, newly developed circulating biomarkers such as free serum amino acids [38] could be compared to CTC or ctDNA detection for their prognostic value. Similarly, circulating extracellular matrix components have been evaluated as biomarkers for cancer diagnosis and prognosis in various tumor types [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, methionine-derivative S-adenosyl methionine (SAM) is a cofactor acting mainly as a methyl donor to cytosine in DNA during epigenetic modification [136]. A recent study found a reduced oral mucositis after an oral D-methionine treatment in patients with grade 3/4 HNSCCs [137]; an in vitro study showed that the administration of methionine could also downregulate the proliferative capacity in HNSCC cells; it was also reported that there was a positive correlation of high methionine serum levels with greater overall and relapse-free survival rates [121,138]. These findings suggest that methionine could be tumor-suppressive and that the methionine content might serve as a prognostic factor for HNSCC patients, although one must still mechanistically clarify the way in which methionine regulates epigenetic modification in HNSCC development.…”
Section: Development Of Anti-cancer Scheme By Targeting Distinct Mmentioning
confidence: 99%
“…Various factors can influence serum AA pattern in cancer, depending on the type and the stage of the disease: muscle wasting, malnutrition, systemic inflammation, and insulin resistance [ 20 , 21 ]. To our knowledge, only one study has specifically addressed the link between the basal serum AA levels and long-term prognosis in HNC patients [ 15 ]. Our study was done on a larger number of patients, with a less unbalanced female/male patient ratio, measuring a wider panel of serum AAs and evaluating the impact of AA profiles on both the OS and the risk of advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Glycine uptake and catabolism promote tumorigenesis and malignancy [ 30 ], and its biosynthesis is deemed as a central process in sustaining rapid proliferation [ 11 , 28 ]; serine serves as a central hub in the metabolic network for many aspects of cancer cell survival and proliferation [ 28 ]. Higher concentrations of glycine and serine have been detected in the malignant head and neck squamous cell carcinoma tissue samples compared to surrounding normal tissues [ 15 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation